Narrative discourse deficits in amyotrophic lateral sclerosis - Ash, Sharon (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: We examined narrative discourse in amyotrophic lateral sclerosis (ALS) to assess the role of executive functioning in support of language and the neuroanatomical basis for such support. METHODS: We analyzed a semistructured speech sample in 26 patients with ALS and 19 healthy seniors for narrative discourse features of coherence. Regression analyses related a measure of discourse coherence (“local connectedness”) to gray matter atrophy and reduced white matter fractional anisotropy. RESULTS: Patients with ALS were impaired relative to controls on measures of discourse adequacy, including local connectedness and maintenance of the theme. These discourse measures were related to measures of executive functioning but not to motor functioning. Regressions related local connectedness to gray matter atrophy in ventral and dorsal prefrontal regions and to reduced fractional anisotropy in white matter tracts mediating projections between prefrontal regions. CONCLUSION: Patients with ALS exhibit deficits in their ability to organize narrative discourse. These deficits appear to be related in part to executive limitations. Consistent with the hypothesis that ALS is a multisystem disorder, this deficit is related to disease in prefrontal regions.